Shifting Beliefs on Digital Platforms: The Case of the ‘Godless Utopia’ of Binnur Duman Academy - Merve Bahadur; İhsan Çapcıoğlu (Medya ve Din Araştırmaları Dergisi)
Technological developments and the introduction of mass media into our lives have led to an increase in the visibility of religion on digital platforms. With the digitalization process affecting religious perceptions and practices, the change in the phenomenon of belief has brought about an intensification of spiritual searches. These searches offer almost all belief systems, from institutionalized religions to far eastern religions, from traditional sects to modern community structures, the opportunity to be represented in the digital world. Alternative formations outside of institutionalized religions such as paganism, Hinduism, esotericism, mysticism and occultism open the door to new forms of belief and offer spiritual experiences. Thanks to the channels recommended in reels and live IGVT videos on social networks, individuals have easy access to flexible and versatile spiritual experiences. In this study, the practices such as psychic surgery, return to self, and retreat camp are discussed in the account of the spiritual group named Binnur Duman Academy on the social media application Instagram, which has 545 posts and 813 thousand followers. The study, which applied content analysis, one of the qualitative research techniques, was limited to 15 IGTV video content among 545 posts published between January 2023 and March 2024. The impact of spiritual experiences on religious practice and spiritual quests in IGTV videos was evaluated, and it was analyzed how the rituals in the Instagram posts of the group within the new age movements were recognized on social networks.